Inside Out: A Corpus-Driven Study of Expressions with Parts of the Body in the Albanian Language - Qafzezi, Eriola (Corpora in Language Learning, Translation and Research: Proceedings of the International Conference Corpora in Language Learning, Translation and Research held at the University of Zadar (August 23–24, 2023), 2025)
The aim of this paper is to illustrate expressions with parts of the body in the Albanian language, based on a corpus-driven study. Research that is based on corpora is an area of study yet to be explored in the Albanian language. This is due to the fact that corpora of the Albanian language have only recently been developed, and thus corpus-based linguistic research and/or corpus-driven research present challenging and innovative pursuits. Our study primarily adopts a qualitative approach, based on a corpus-driven analysis, enriched by a few quantitative data that show the number of occurrences of linguistic expressions for each part of the body under investigation. We have extracted examples from the Albanian National Corpus (ANC). We begin the paper by presenting the research questions and then we outline some relevant literature background. The corpus and methodology of the study are described in the third section, followed by the analysis and discussion of the data in the fourth section. The paper ends with conclusions based on the current research and suggestions on how to extend the study in the future.